Research on sports health communication in Guangzhou, China in the context of "Healthy China 2030" - Wei, Cheng; Yossakrai, Asst.Prof.Dr. Kanokrat; Patananukit, Dr.Nutcha (Journal of Dhamma for Life, 2023)
The research objectives were as follows: (1) To examine the state of communication regarding sport health policy based on "HEALTHY CHINA 2030" in China; (2) To investigate the health communication process in sports based on "HEALTHY CHINA 2030" in China; (3) To analyze the problems and obstacles in sports health communication based on "HEALTHY CHINA 2030" in China; and (4) To explore health communication guidelines in sports based on "HEALTHY CHINA 2030" in Guangzhou, China. The primary theoretical frameworks employed were sport health communication, uses and gratification, and Bourdieu’s Habitus. This study adopted a mixed-methods approach. Quantitative analysis involved studying a sample of 18,734,100 individuals aged 18 to 60 in Guangzhou, China, with 410 samples collected through non-probability sampling. In-depth interviews were conducted with key informants, including representatives from public sports health organizations in Guangzhou, sports event marketing companies, media practitioners, and university professors. Data collection utilized online questionnaires, literature reviews, and in-depth interviews, with descriptive statistics and Pearson correlation analysis employed for data analysis. Key findings included: (1) The communication of the "HEALTHY CHINA 2030" policy in 2023 faced initial challenges in gaining popularity; (2) The sport health communication process revealed varying levels of presentation of "Healthy China 2030" by both public and private organizations in Guangzhou. Messages predominantly emphasized the health benefits of sports in daily life, with mixed media usage, where online platforms proved more efficient. However, normative management was lacking; (3) Identified problems and obstacles included limited choices of communication channels and insufficient personalized information; and (4) To enhance communication effectiveness, recommendations included strengthening policy publicity, adopting multi-channel communication, customizing content, and promoting health concepts comprehensively.